Effect of Pineapple Peel on Enzyme Production and Antioxidant Potential in Scoby Fermentation (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
The study demonstrated that pineapple peel supplementation enhances microbial activity and enzyme production in kombucha fermentation, with the Symbiotic Culture of Bacteria and Yeast (SCOBY) brewing solution exhibiting a rapid pH decline to 2.96 within 7 days due to organic acid production from acetic acid bacteria and yeasts, ensuring a safe fermentation environment (pH ≤ 4.6). Pineapple peels sustained microbial populations such as yeast, lactic acid bacteria (LAB) and acetic acid bacteria (AAB) at 37 °C, but at 45 °C it caused severe inhibition due to thermal stress, while acting as nutrient sources to support higher cell counts (AAB: 2,620 CFU/mL) compared to controls. This study evaluated protease, cellulase, and lipase activities at 37 °C and 45 °C using agar plate hydrolysis assays. Protease exhibited activity, with hydrolysis indices of 2.2-2.3 at 37 °C and 3.0 at 45 °C, demonstrating temperature-enhanced performance consistent with bromelain’s thermal optima. Cellulase showed peak activity at 37 °C (index 2.4, day 3), declining thereafter, while 45 °C sustained higher indices (2.1-3.3), indicating thermal stability. Lipase displayed moderate activity at 37 °C (index 2.5, day 6) but improved at 45 °C (index 2.7, day 3), aligning with prior reports on thermophilic activation. The results highlight pineapple peels as an effective substrate for thermostable protease and cellulase production, with potential applications in bioconversion processes.
Keywords: Bacterial Cellulose; Kombucha; Pineapple Peel; Fermentation; Acetic Acid Bacteria